Effect of Different Fertilizations on the Plant-Available Nitrogen in Soil Profile (0–100 cm): A Study on Chinese Cabbage - Ahmed, Rasheed; Mao, Lili; Li, Yuzhong; Ding, Junjun; Lin, Wei; Ahmed, Shakeel; Abbas, Asad; Ahmed, Waseem (Frontiers in Plant Science, 2022)
The aim of this study is to analyze the variations in the plant-available nitrogen (PAN) concentrations in the soil profile. Different fertilizers were applied for Chinese cabbage plantation (CCP) in the experimental fields of the Shunyi region. The treatments used for the comparative analysis are (i) no fertilizer and plantation (NVP), (ii) no fertilizer with CCP (CTP), (iii) fertilization as urea (URP), and (iv) potassium nitrate (KNP) and chicken manure (CMP) with CCP. It was concluded that the yield was significantly high in URP, CMP, and KNP as compared to CTP. In URP, maximum PAN in soil layers 0–60 cm was recorded during crop production and in 60–100 cm after harvesting as compared to other treatments. Significant variations in soil pH and electrical conductivity (EC) for the soil profile (0–100 cm) from the initial values with respect to time and treatments were observed. CMP showed maximum ammonium in the upper layers of 0–60 cm throughout the season, whereas minimum PAN was observed in NVP but increased in lower layers of 60–100 cm. In general, all fertilizers raised the PAN below the soil 60–100 cm which indicates their potential for nitrate leaching (NL).